A comtetency model for foster parents in caring abused children - Olga Baydarova; Polina Klikova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
In the article, results of empirical research of the competencymodel for foster parents in caring abused children are presented. This model in- cludes two topics, such as the ability to respond to the consequences of child abuse and neglect,and the ability to create healing environment for children through specific knowledge, understanding and skills.